Filosofi Team Work dalam Pelayanan Paulus dan Barnabas - Nggebu, Sostenis (SAINT PAUL'S REVIEW, 2025)
This article examines the philosophical value of teamwork in the ministry of the Apostles Paul and Barnabas, especially in the first period of evangelistic missions (Acts 13-14). Paul and Barnabas point to an example of effective and impactful cooperation in church ministry, focusing on outreach to Gentiles without imposing Jewish tradition. This study uses the study method of theological literature to analyze the dynamics of their teamwork and its relevance to the church in the postmodern era. The results of the study show that teamwork is not only a method, but an important foundation in church ministry. Effective cooperation increases efficiency, expands reach, and builds strong communities, while reflecting the essence of the church as the body of Christ. The philosophical values of Paul and Barnabas' teamwork, such as synergy, unity in diversity, and focus on mission, remain relevant and applicable to improve the quality of church service today.